Influence of toothbrushing on enamel softening and abrasive wear of eroded bovine enamel: an in situ study Influência da escovação no amolecimento superficial do esmalte e desgaste do esmalte bovino erodido: um estudo in situ - Daniela Rios; Heitor Marques Honório; Ana Carolina Magalhães; Marília Afonso Rabelo Buzalaf; Regina Guenka Palma-Dibb; Maria Aparecida de Andrade Moreira Machado; Salete Moura Bonifácio da Silva (Sociedade Brasileira de Pesquisa Odontológica, 2006)
This study assessed the surface softening and abrasive wear of eroded bovine enamel with or without the influence of toothbrushing. Five volunteers took part in this in situ study of 5 days. They wore acrylic palatal appliances containing 6 bovine enamel blocks divided in two rows with 3 blocks, which corresponded to the studied groups: erosion without toothbrushing (GI) and erosion with toothbrushing (GII). The blocks were subjected to erosion by immersion of the appliances in a cola drink for 10 minutes, 4 times a day. After that, no treatment was performed in one row (GI), whereas the other row was brushed (GII). The appliance was then replaced into the mouth. Enamel alterations were determined using profilometry and microhardness tests. Data were tested using paired Student's t test (p < 0.05). The mean wear values (µm) and percentage of superficial microhardness change (%SMHC) were respectively: GI - 2.77 ± 1.21/91.61 ± 3.68 and GII - 3.80 ± 0.91/58.77 ± 11.47. There was a significant difference in wear (p = 0.001) and %SMHC (p = 0.001) between the groups. It was concluded that the wear was more pronounced when associated to toothbrushing abrasion. However, toothbrushing promoted less %SMHC due to the removal of the altered superficial enamel layer. Este estudo avaliou o amolecimento superficial e o desgaste do esmalte bovino erodido com ou sem influência da escovação. Cinco voluntários fizeram parte deste estudo in situ de 5 dias. Eles usaram aparelhos palatinos de acrílico contendo 6 blocos de esmalte bovino divididos em 2 fileiras com 3 blocos, cada fileira correspondeu a um grupo em estudo: erosão sem escovação dentária (GI) e erosão seguida de escovação dentária (GII). Os blocos foram submetidos à erosão por imersão do aparelho em uma bebida à base de cola por 10 minutos, 4 vezes ao dia. Depois disso, nenhum tratamento foi realizado em uma fileira (GI), enquanto a outra fileira foi escovada (GII). Em seguida, o aparelho foi recolocado na boca. Alterações do esmalte foram determinadas por teste de perfilometria e microdureza. Os dados foram analisados usando-se teste t de Student (p < 0,05). O valor médio de desgaste (µm) e da porcentagem de perda de microdureza superficial (%PDS) foi respectivamente: GI - 2,77 ± 1,21/91,61 ± 3,68 e GII - 3,80 ± 0,91/58,77 ± 11,47. Houve uma diferença estatisticamente significante no desgaste (p = 0,001) e na %PDS (p = 0,001) entre grupos. Conclui-se que o desgaste foi mais pronunciado quando associado à abrasão pela escovação. Entretanto, a escovação promoveu menor %PDS, devido à remoção da camada de esmalte superficial alterada.